Blending Automation and Human Expertise in SRE for Banking Applications (Global Journal of Computer Science and Technology, 2025)
The banking sector presents unique challenges for Site Reliability Engineering practices due to stringent regulatory requirements complex technical environments and zero-tolerance for financial data errors This article explores the critical balance between automation capabilities and human expertise in maintaining reliable banking applications It examines the distinctive reliability requirements of financial systems identifies effective automation strategies within regulatory constraints articulates the irreplaceable components of human judgment and proposes an implementation framework for optimal collaboration between automated systems and human operators Through detailed analysis of banking-specific failure modes monitoring approaches and incident response workflows the article provides a structured approach to developing SRE practices that leverage both technological capabilities and human cognitive strengths while respecting the unique constraints of financial environments The framework presented enables banking institutions to implement reliability practices that maintain transaction integrity meet regulatory obligations and support business objectives through carefully designed human-automation systems
Keywords: banking SRE; automation boundaries; regulatory compliance; human judgment; transaction integrity